CONSTANS Polymorphism Modulates Flowering Time and Maturity in Soybean - Awal Khan, Mohammad Abdul; Zhang, Shouwei; Emon, Reza Mohammad; Chen, Fulu; Song, Wenwen; Wu, Tingting; Yuan, Shan; Wu, Cunxiang; Hou, Wensheng; Sun, Shi; Fu, Yongfu; Jiang, Bingjun; et al. (Frontiers in Plant Science, 2022)
CONSTANS (CO) plays a critical role in the photoperiodic flowering pathway. However, the function of soybean CO orthologs and the molecular mechanisms in regulating flowering remain largely unknown. This study characterized the natural variations in CO family genes and their association with flowering time and maturity in soybeans. A total of 21 soybean CO family genes (GmCOLs) were cloned and sequenced in 128 varieties covering 14 known maturity groups (MG 0000-MG X from earliest to latest maturity). Regarding the whole genomic region involving these genes, GmCOL1, GmCOL3, GmCOL8, GmCOL9, GmCOL10, and GmCOL13 were conserved, and the remaining 15 genes showed genetic variation that was brought about by mutation, namely, all single-nucleotide polymorphisms (SNPs) and insertions-deletions (InDels). In addition, a few genes showed some strong linkage disequilibrium. Point mutations were found in 15 GmCOL genes, which can lead to changes in the potential protein structure. Early flowering and maturation were related to eight genes (GmCOL1/3/4/8/13/15/16/19). For flowering and maturation, 11 genes (GmCOL2/5/6/14/20/22/23/24/25/26/28) expressed divergent physiognomy. Haplotype analysis indicated that the haplotypes of GmCOL5-Hap2, GmCOL13-Hap2/3, and GmCOL28-Hap2 were associated with flowering dates and soybean maturity. This study helps address the role of GmCOL family genes in adapting to diverse environments, particularly when it is necessary to regulate soybean flowering dates and maturity.